WISATA AGRIBISNIS SEBAGAI PRODUK PENGEMBANGAN USAHA INTELEKTUAL KAMPUS - Hartati; Ahmad Muhlis Nuryadi; Herdianto Husein (LP2M Universitas Hasanuddin, 2023)
Agribusiness Tourism is a business managed by maximizing tourism-based culinary business activities. The main objective of these community activities is to accelerate the process of developing entrepreneurship oriented to local culinary products. This effort involves students of the Agribusiness Study Program Faculty of Agriculture and Management Study Program, Faculty of Economics and Islamic Business (FEBI). This activity provides experience and job opportunities for students open employment opportunities for the community and provide culinary needs in the form of traditional foods of Southeast Sulawesi (sinonggi) and healthy, fresh and delicious seafood for customers. The method of carrying out the activities consists of socializing, training, providing infrastructure and facilities, promotion, and marketing. This activity is carried out in the area of ​​embankments that were previously less productive with relatively low income. The location is in the Poasia District of Kendari, Southeast Sulawesi. To accelerate the process of developing entrepreneurship, the activity is designed by changing a traditional embankment into an agribusiness tourism specific to local culinary tourism by designing a gazebo building as a place to enjoy culinary menu orders. The location has its characteristics with the design of the place based on agribusiness decorated with ornamental plants, pollution-absorbing plants, hydroponic plants, and organic vegetable plants. Visitors can enjoy the natural scenery through the embankment garden design in the form of selfie spots for visitors. The results of the implementation of the activity are in the form of a business unit